The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/jnn.0000000000000654
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Family Caregiver Life Changes From the COVID-19 Pandemic

Abstract: BACKGROUND: Stroke family caregivers were already struggling with unmet needs and changes in their own lives from providing care. The COVID-19 pandemic added further stress and disruption to their lives. The purpose of this study was to describe life changes in 17 stroke family caregivers specifically resulting from the COVID-19 pandemic. METHODS: This study was conducted as a secondary data analysis from an ongoing randomized controlled clinical trial testing feasibility of the Telehealth Assessment and Skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Strokes develop with lifestyle-related diseases or atrial fibrillation as significant risk factors and have been found to have a high recurrence rate, 1 especially in the early stage of onset. 2 Stroke patients develop more severe diseases because of recurrence, [3][4][5] it is crucial to control their risk factors with self-management to prevent recurrence. 6 However, in Japan only a low percentage of stroke patients receive adequate educational intervention to help control risk factors with self-management.…”
Section: Introductionmentioning
confidence: 99%
“…Strokes develop with lifestyle-related diseases or atrial fibrillation as significant risk factors and have been found to have a high recurrence rate, 1 especially in the early stage of onset. 2 Stroke patients develop more severe diseases because of recurrence, [3][4][5] it is crucial to control their risk factors with self-management to prevent recurrence. 6 However, in Japan only a low percentage of stroke patients receive adequate educational intervention to help control risk factors with self-management.…”
Section: Introductionmentioning
confidence: 99%